PteridophytaE-Encyclopedia of Kelud Mountain to Study of the Diversity of Fern Species in the Environment on the RICOSRE Model to Improve Student’s Information Literacy - Dwi Ayuningtyas; Paramita Cahyaningrum Kuswandi (Postgraduate, University of Mataram, 2024)
The low level of information literacy and the lack of utilization of local potential is one of the reasons to develop the learning innovations. One of innovation is utilize local potential as a learning resource in the form of an e-encyclopedia and integrate it with the RICOSRE learning model. This research aims to determine the feasibility, practicality, and effectiveness from the pteridophyta e-encyclopedia of Kelud Mount for studying the diversity of fern species on RICOSRE model to increase information literacy. This research uses the development research with the ADDIE design and implemented in class X of students at SMA Negeri 1 Talun. The instruments research were questionnaires and information literacy rubrics. The data result was analyzed using the percentage equation, while information literacy data was analyzed with N-Gain equation and Independent Sample T-Test. The research results show that the pteridophyta e-encyclopedia are feasible by lecturer and stated to be practical by teachers and students. The conclusion is the information literacy of students who use e-encyclopaedia’s in RICOSRE learning is proven to be higher than students who do not use it.